Taxation of undeclared income in Montenegro: constitutional challenges - Vukcevic, Ilija; Boskovic, Mirko (Transformations In Business & Economics, 2025)
In this study, we survey and analyse the system of taxation of ‘undeclared income’, which essentially refers to cross-assessment of the tax base by the tax authority, which is carried out in situations where the reported income is many times smaller than the property and consumption of a certain individual. In these situations, the tax authorities have provisions at their disposal that give them the opportunity to determine the value of taxpayers’ property and consumption, so that if this value is significantly higher than the amount of income they have declared, the authorities have the right to tax the difference. We identify the shortcomings of the subject fiscal mechanism, due to which the competent authority never applied them in practice. A special focus is placed on the issue of the compatibility of these provisions with the Constitution of Montenegro, and the violation of several constitutional principles in the practice of the Constitutional Court of Montenegro will be pointed out. It has been found that the legislator does not properly understand the aim and the role of these fiscal provisions in the overall context of reviewing the origin of property.